Molecular profiling of foxtail millet (Setaria italica (L.) P. Beauv) from Central Himalayan Region for genetic variability and nutritional quality. (28th May 2018) - Trivedi, A. K.; Arya, L.; Verma, S. K.; Tyagi, R. K.; Hemantaranjan, A.; Verma, M.; Sharma, V. P.; Saha, D.
Abstract: Agriculture in the Central Himalayan Region depends on the availability of suitable germplasm as well as natural conditions. Due to extreme weather conditions, food and nutrition security is a major issue for communities inhabiting these remote and inaccessible areas. Millets are common crops grown in these areas. Foxtail millet ( Setaria italica (L.) P. Beauv) is an important crop and forms a considerable part of the diet in this region. The aim of the present study was to explore, collect, conserve and evaluate the untapped genetic diversity of foxtail millet at the molecular level and discover variability in their nutritional traits. A total of 30 accessions having unique traits of agronomic importance were collected and molecular profiling was performed. A total of 63 alleles were generated with an average of 2.52 alleles per locus and average expected heterozygosity of 0.37 ± 0.231. Significant genetic variability was revealed through the genetic differentiation (Fst) and gene flow (Nm) values. Structure-based analysis divided whole germplasm into three sub-groups. Rich variability was found in nutritional traits such as dietary fibre in husked grains, carbohydrate, protein, lysine and thiamine content. The collected germplasm may be useful for developing nutritionally rich and agronomically beneficial varieties of foxtail millet and also designing strategies for utilization of unexploited genetic diversity for food and nutrition security in this and other similar agro-ecological regions.